Model of Competency Evaluation on Learning Management in Basic Education Level for Student Teachers of Rajabhat Universities - Sirisawas Thongkanluang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study had objectives to develop factors and indicators of competency in learning management at basic education level, study and analyze the competency evaluation model, construct, trial, and search for the value competency evaluation model for learning management apart from examining the validity of the causal relationships of learner quality at basic education level with the empirical data applying R&D process, that is, 4 research phases: development of factors and indicators for competency in learning management having effects on learner quality at basic education level, documentary analysis of competency evaluation model, construction and trial of the competency evaluation model in learning management at basic education level for student teachers of Rajabhat universities, and verify the causal relationships of student teachers in Rajabhat universities that influenced the quality of learners at basic education level. The population and samples were 14 expert staffers of assessment of indicators and factors; 3 groups of people concerning in the competency evaluation model: 95 curriculum committee members and advisor instructors, 424 school administrators and overseeing teachers, and 678 student teachers. The tools employed in data collection were questionnaires, record forms for focus-group discussion, and a model of competency evaluation on learning management. The quality data analysis comprised frequency, percent, mean, standard deviation, t-test, one-way ANOVA, Scheffe's multiple comparison test, Chi-square test, and structural equation modeling analysis as well as content analysis. It was found that: 1. The development of factors and indicators for competency in learning management at basic education for student teachers in Rajabhat universities revealed that there were 4 factors and 12 indicators: the knowledge factor consisted of 2 indicators, that is, teaching profession knowledge and content arrangement knowledge; the characteristic factor consisted of 2 indicators, that is, teacher characteristic and attitudes towards the teaching profession; learning management factor consisted of 6 indicators, that is, learner analysis, learning design, learning management preparation, learning process organization, evaluation learning, and improvement and research for development in learning management; and learner quality factor consisted of 2 indicators, that is, learning achievement and learning person characteristic. 2. The model of competency evaluation on learning management in basic education level for student teachers of Rajabhat universities was composted of 2 parts, that is, part 1: the issues to evaluate, the background, and significant points of the competency in learning management; and part 2: the evaluation method, evaluation concepts, objective of the evaluation, evaluation framework, evaluation tool, evaluation process, judgment of competency level, and application of the evaluation. The evaluation model was used in an applicable manner mainly with the authentic assessment and having it integrate with the Tyler’s objective evaluations model, Provus' discrepancy evaluation model, Fetterman’s empowerment evaluation model, and Council and Earl’s participatory evaluation model. The evaluation model was tried out with the sample student teachers of 179 Rajabhat universities. The outputs were scores and quality levels of indicators, sub competencies and a summative competency in learning management for each student teacher, program of study and university. As regards the quality of evaluation model resulted from the opinions having had from the 3 evaluator groups comprising 22 advisor instructors, 126 overseeing teachers, and 166 student teachers, it revealed that the evaluation model constructed and developed, as a whole, was accurate, valid, reliable, appropriate, and useful; the mean opinion level of the evaluation model was 4.47 or regarded as very high level. 3. The causal relationship model of student teachers that had effects on learner quality at basic education level having been constructed was in consistency and in harmony with the empirical data with Chi-square at 7.68, df = 16, p = 0.96, 2/df = 0.48, RMSEA = 0.00, RMR = 0.02, Standardized RMR = 0.01, GFI = 0.99, AGFI = 0.97 and Q-plot; having more steepness than the diagonal lines. The evaluation model comprised of 12 variables. As regards the structural model, it revealed that there were student teachers factors which had effects on learner quality, in this order of importance: learning management, characteristic, and knowledge, respectively, 94 percent of the covariance in the learner quality latent variables could be explained.